2015
DOI: 10.1177/0899764015583121
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit Influence on Public Policy

Abstract: This article examines the advocacy tactics of Russian nonprofits. While Russian nonprofits and their activities have been widely researched, specific insight into their use of advocacy tactics remains limited. In this article, we address this gap by broadening the understanding of how Russian nonprofits engage in advocacy. To do so we engage both Mosley’s indirect/insider framework and qualitative data collected from health and education nonprofits (HEnonprofits) in three Russian industrial regions. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…In addition, social service providers typically participate in consultative bodies on social policy issues at the federal and regional level, such as public chambers and parliamentary working groups (Fröhlich, 2012). Furthermore, service-providing NGOs have developed a broad range of informal and formal advocacy activities to represent their clientele without questioning the dominance of the state (Ljubownikow & Crotty, 2015; Toepler & Fröhlich, 2020), and with a preference for collaborative, insider advocacy (Pape & Skokova, 2022).…”
Section: Discussion: Applying the Typology To The Cases Of Russia And...mentioning
confidence: 99%
“…In addition, social service providers typically participate in consultative bodies on social policy issues at the federal and regional level, such as public chambers and parliamentary working groups (Fröhlich, 2012). Furthermore, service-providing NGOs have developed a broad range of informal and formal advocacy activities to represent their clientele without questioning the dominance of the state (Ljubownikow & Crotty, 2015; Toepler & Fröhlich, 2020), and with a preference for collaborative, insider advocacy (Pape & Skokova, 2022).…”
Section: Discussion: Applying the Typology To The Cases Of Russia And...mentioning
confidence: 99%
“…In contrast with the research claiming marketisation of the social sector threatens civil society in the USA (Eikenberry 2009;Eikenberry and Kluver 2004;Nickel and Eikenberry 2009), this study suggests that social marketisation in fact can strengthen the development of civil society, by enhancing the policy influence of social sector organisations. Secondly, this research responds to the call to add the diversity to the understanding of policy influence or advocacy in different country contexts, as the majority of the scholarship is based on experiences of social sector organisations in the USA (Almog-Bar and Schmid 2014;Ljubownikow and Crotty 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown, however, that NGOs do advocate to influence authoritarian governments. Ljubownikow and Crotty (2016), for example, find that NGOs in Russia tend to use limited indirect and institutionalized insider advocacy tactics. Why do authoritarian governments like China, which typically do not tolerate civil society groups, then allow NGOs to advocate?…”
Section: Ngo Policy Advocacy In Authoritarian Regimesmentioning
confidence: 99%